Influence of post‐annealing ambient gas on photoluminescence characteristics for ion beam synthesized Ge nanoparticles in SiO2 and Si3N4 films. (15th May 2014) - Yu, C. F.; Chao, D. S.; Tsai, H. S.; Liang, J. H.; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> Ion beam synthesized Ge nanoparticles in SiO2 film have received intense interest due to their distinctive optical features. Nevertheless, the fundamental mechanism behind luminescence from Ge nanoparticles still remains under debate. In order to investigate the influence of oxygen content on the optical properties of Ge nanoparticles, post‐annealing treatments under various annealing atmospheres including vacuum, air, and N2 were conducted to synthesize Ge nanoparticles. An oxygen‐free Si3N4 matrix material was also adopted to compare with the results of SiO2 one. The results revealed that photoluminescence (PL) around 3.1 eV can be emitted from Ge‐implanted SiO2 films. However, Ge‐implanted SiO2 films appear remarkably diverse PL characteristics when annealed in different ambient gases. PL intensity fluctuates with temperature in the specimens annealed under vacuum and air due to the GeOx formation and dissolution. Otherwise, the N2‐annealed specimens can suppress germanium oxidation process, thus allowing for an entirely different evolution of PL intensity with temperature. In contrast to the SiO2 matrix, no PL emission can be found for the Ge nanoparticles formed in the Si3N4 films, again proving that the 3.1‐eV emission band indeed originates from the oxygen‐deficient centers at the interface between SiO2 matrix and Ge or GeOx nanoparticles. Copyright © 2014 John Wiley & Sons, Ltd.